2010
DOI: 10.7205/milmed-d-09-00088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Six Weeks of Quercetin Supplementation on Physical Performance in ROTC Cadets

Abstract: Six weeks of dietary quercetin supplementation in moderately trained individuals conducting military physical training did not improve VO(2peak) or performance on the APFT, BMPU, WAnT, and 36.6-m sprint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 28 publications
4
20
1
Order By: Relevance
“…However, as described above, no differences were observed in any groups on measures related to oxygen uptake by quercetin supplementation. These results are similar to those obtained by Bigelman et al [30]. There are several potential reasons for these results: firstly, VO 2 peak is influenced by muscle mitochondrial oxidative capacity, but relative to endurance capacity, it is limited to a greater extent by oxygen delivery via the cardiovascular system [31].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, as described above, no differences were observed in any groups on measures related to oxygen uptake by quercetin supplementation. These results are similar to those obtained by Bigelman et al [30]. There are several potential reasons for these results: firstly, VO 2 peak is influenced by muscle mitochondrial oxidative capacity, but relative to endurance capacity, it is limited to a greater extent by oxygen delivery via the cardiovascular system [31].…”
Section: Discussionsupporting
confidence: 87%
“…This could be a more appropriate supplement to increase oxygen consumption [16]. However, previous work did not find any ergogenic effect of quercetin and EGCG supplementation in a moderately trained sample [30]. …”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that the placebo group in this study had a 1.5% performance improvement. The study by Bigelman et al15 found no significant difference in VO 2peak or anaerobic performance measures with 6 weeks of quercetin supplementation in moderately trained military personnel. Neither of these two studies investigated the antioxidant effects of quercetin supplementation.…”
Section: Introductionmentioning
confidence: 93%
“…Although quercetin supplementation shows potential endurance performance benefits in cell culture and in vivo animal studies [160, 161], research on its use as a supplement in humans are less clear. Some studies have reported increased endurance exercise capacity and performance in humans following supplementation with quercetin [162164]; however, many have failed to find benefits [165171]. Of the 2 studies [172, 173] on ultra-endurance trained subjects, both have shown no significant benefit.…”
Section: Reviewmentioning
confidence: 99%